Targeting endoplasmic reticulum stress: an innovative therapeutic strategy for podocyte-related kidney diseases - Jiao Lv; Honghai Yu; Sasa Du; Pengyu Xu; Yunyun Zhao; Wenxiu Qi; Xiuge Wang (Journal of Translational Medicine)
Abstract The endoplasmic reticulum (ER) is a vital organelle responsible for protein quality control, including the folding, modification, and transport of proteins. When misfolded or unfolded proteins accumulate in the ER, it triggers endoplasmic reticulum stress (ERS) and activates the unfolded protein response (UPR) to restore ER homeostasis. However, prolonged or excessive ERS can lead to apoptosis. The kidneys play a crucial role in maintaining physiological functions by excreting metabolic waste, regulating blood volume, balancing electrolytes and acid-base levels, and secreting various bioactive substances. Podocytes, epithelial cells situated outside the glomerular basement membrane, are essential for maintaining the structural integrity and permeability of the glomerular filtration barrier. Previous studies have shown that ERS in podocytes can contribute to the development of diseases such as glomerulonephritis, hereditary nephropathy, and diabetic kidney disease, potentially progressing to end-stage renal disease and causing patient mortality. As such, investigating ERS in podocytes has become a key area of focus in kidney disease research. This study examines recent advancements in understanding the effects of excessive ERS on podocytes across various kidney diseases, highlights the role of podocyte ERS in disease progression, and explores the potential therapeutic benefits of targeting the UPR to manage ERS in kidney diseases, thereby providing a scientific basis for clinical interventions. Graphical Abstract